UV-Vis spectrophotometry and chemometrics as tools for recognition of the biochemical profiles of organic banana peels (Musa sp.) according to the seasonality in southern Brazil - Lopes, Susane (2017)
Banana (Musa sp.) has received wide interest in popular and scientific medicine because of its rich composition in bioactive metabolites, e.g., phenolic compounds, found in interesting concentrations in its peel. Banana peel is a residue that is under-exploited by the industry. Thus, with the intention to give a destination to this by-product towards health care or cosmetics industries, we evaluated its aqueous extract (AE) as a source of bioactive phenolic compounds, aiming at to apply them in future studies of biological activities. For that, in this study samples of banana peels were chemically profiled throughout the year to identify the best harvest time of those biomasses regarding their phenolic composition. In this sense, we used additional information on the chemical heterogeneity of the samples determined by the seasoning, through a set of analytical and climatic data to elaborate chemometric models, supported by bioinformatics tools. Through PCA and HCA analyzes, it was detected that low temperatures; normally observed in winter; strongly modulate the banana metabolism, leading to increased amounts of phenolic compounds, and improving the antioxidant activity of the banana peel AE. The samples collected during the months of winter showed a similar profile and a relatively high concentration of phenolic compounds with potential for future studies of biological activities.